2021
DOI: 10.1126/scisignal.abf0322
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodesmata-localized proteins and ROS orchestrate light-induced rapid systemic signaling in Arabidopsis

Abstract: Systemic signaling and systemic acquired acclimation (SAA) are key to the survival of plants during episodes of abiotic stress. These processes depend on a continuous chain of cell-to-cell signaling events that extends from the initial tissue that senses the stress (the local tissue) to the entire plant (systemic tissues). Reactive oxygen species (ROS) and Ca2+ are key signaling molecules thought to be involved in this cell-to-cell mechanism. Here, we report that the systemic response of Arabidopsis thaliana t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(149 citation statements)
references
References 54 publications
4
145
0
Order By: Relevance
“…We were not able to confirm that NADPH oxidase activity is strongest in BSS, so it is possible that they produce the ROS in the mesophyll and that aquaporins then transport ROS to the bundle sheath. If true, this would be analogous to the role of aquaporins in mediating the long-distance high-light systemic signal (27). However, it does appear that specific isoforms of NADPH oxidase are responsible for this high-light response.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We were not able to confirm that NADPH oxidase activity is strongest in BSS, so it is possible that they produce the ROS in the mesophyll and that aquaporins then transport ROS to the bundle sheath. If true, this would be analogous to the role of aquaporins in mediating the long-distance high-light systemic signal (27). However, it does appear that specific isoforms of NADPH oxidase are responsible for this high-light response.…”
Section: Discussionmentioning
confidence: 94%
“…Such ROSmediated systemic signaling from a locally perturbed leaf can lead to stomatal aperture being altered in distant leaves, is associated with the hormones abscisic and jasmonic acid, and is dependent on the plasma membrane-localized NADPH oxidase (AtRBOHD and AtRBOHF) in cells of the phloem and xylem (22)(23)(24)(25)(26). Grafting experiments indicate that the initial local propagation of ROS is dependent on respiratory burst oxidase homolog (RBOH) proteins as well as increased cell-to-cell transport that is dependent on plasmodesmata-localized proteins 1 and 5 as well as aquaporins and Ca 2+ -permeable channels in the glutamate receptor-like, mechanosensitive small conductance-like, and cyclic nucleotide-gated families (27).…”
mentioning
confidence: 99%
“…Among the different signaling processes thought to mediate such rapid long distance cell‐to‐cell signal transduction mechanisms in plants are changes in membrane potentials (i.e., electric waves; Farmer et al ., 2020; Hedrich and Fukushima, 2021; Mousavi et al ., 2013; Nguyen et al ., 2018; Shao et al ., 2020; Szechyńska‐Hebda et al ., 2010), steady‐state levels of calcium (i.e., calcium wave; Choi et al ., 2014; Choi et al ., 2017; Dubiella et al ., 2013; Evans et al ., 2016; Shao et al ., 2020; Tian et al ., 2020; Toyota et al ., 2018), steady‐state levels of reactive oxygen species (ROS; i.e., ROS wave; Fichman et al ., 2019; Fichman and Mittler, 2020b; Kollist et al ., 2019; Lew et al ., 2020; Miller et al ., 2009; Mittler et al ., 2011; Zandalinas et al ., 2019; Zandalinas et al ., 2020a; Zandalinas et al ., 2020b), hydraulic pressure (i.e., hydraulic wave; Christmann et al ., 2013; Malone, 1992; Sade et al ., 2014), as well as rapid changes in the levels of different plant hormones such as jasmonic acid (JA), abscisic acid (ABA) and auxin (Devireddy et al ., 2018; Galvez‐Valdivieso et al ., 2009; Guo et al ., 2016; Kangasjärvi et al ., 2009; Wang et al ., 2019), small peptides (Takahashi et al ., 2018), redox levels (Fichman and Mittler, 2021), and/or different metabolites/metabolic signatures (Choudhury et al ., 2018). Recent studies demonstrated that many of these signals propagate from cell‐to‐cell through the vascular bundles of plants using tissues such as xylem parenchyma and phloem cells to mediate systemic electric, calcium and ROS signals, and xylem cells to mediate hydraulic pressure signals (Christmann et al ., 2013; Fichman et al ., 2021; Mousavi et al ., 2013; Nguyen et al ., 2018; Shao et al ., 2020; Toyota et al ., 2018; Zandalinas et al ., 2020a; Zandalinas et al ., 2020b; Zandalinas and Mittler, 2021). In addition, the calcium channels glutamate receptor‐like (GLR) 3.3 and 3.6 were found to pla...…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that callose deposition might impact later responses since callose deposition-mediated plasmodesmata closure can take hours to days to occur 38,[50][51][52][53] . Another possibility is that callose deposition might have a different function early-on, for instance early ROS signaling which is thought to mediate callose deposition, actually increases cell-to-cell communication in leaves 54 .…”
Section: Discussionmentioning
confidence: 99%